Bibliometric analysis of traditional Chinese medicine in cancer treatment via immune system modulation (2015–2025) - Lei, Youfeng; Chen, Chunyan (Frontiers in Immunology, 2025)
ObjectiveThe application of Traditional Chinese Medicine (TCM) in treating cancer by regulating the immune system has garnered significant attention in the academic community. However, comprehensive quantitative analyses in this field remain limited. This study aims to assess the research progress and key trends over the past decade, providing a framework for future studies.MethodsA comprehensive literature search was conducted on the application of TCM in treating cancer by regulating the immune system from 2015 to 2025 using the Web of Science database. The search terms mainly included cancer, Traditional Chinese Medicine, immunity and so on. Data were analyzed and visualized using Origin, R software, VOSviewer, and CiteSpace.ResultsA total of 2,459 articles were included in the analysis. The number of related publications has steadily increased since 2015. China leads in publication volume and plays a crucial role in international collaboration. The Journal of Ethnopharmacology is the leading journal in this field, publishing a substantial number of highly cited studies. Key research areas include keywords such as “apoptosis,” “expression,” “inflammation,” “extract,” “in vitro,” “activation,” “antioxidant,” and “NF-kappa B,” focusing on exploring the role, mechanisms, and efficacy of TCM in modulating immune responses.ConclusionResearch interest in TCM’s role in treating cancer through immune system regulation continues to grow, underscoring its potential in cancer therapy. Current research primarily focuses on the mechanisms by which TCM treats cancer through the modulation of immune cell functions, inhibition of tumor immune evasion, and regulation of immune-related signaling pathways. It also explores its clinical applications and the potential for enhancing the efficacy of immunotherapy.